Transfusion, conservation of blood and blood components in dogs and cats - Nonato Colares Camargo Júnior , Raimundo; Beatriz Pantoja Neves , Ana; Peleja Vinholte , Brena; Junott Miranda , Matheus; Marinho Guimarães , Edicleya; Ribeiro Batista , Helder; Simone Sarmento Gomes , Jaciara; Sousa de Oliveira , Albiane; Claudia de Sousa Lins , Anna; Conceição da Silva , Welligton (Seven Editora, 2023)
Transfusion therapy in veterinary medicine is a practice that is growing more and more, being used as a supportive treatment for dogs and cats, mainly with the use of whole blood, which seeks to reestablish the ability to transport oxygen to tissues, in addition to correcting other deficits, as in the case of severe anemias and blood losses. Although there are still indications for the use of whole blood, currently the bags are centrifuged for separation of blood components, favoring the more economical use of whole blood. The blood enabled to the transfusion process should be stored in plastic bags, however, during the conservation period, the blood tissue suffers increasing lesions, and these changes are known together as storage lesions. Deficiency in monitoring these changes over the preservation period may make blood use unfeasible or decrease its effectiveness after transfusion. Therefore, it is important to  disseminate information about the whole process, as well as the correct use of blood components, in order to subsidize donation programs and veterinary blood banks.  This chapter aims to conduct a literature review to highlight advances in transfusion medicine and the conservationof blood and blood components in dogs and cats. DOI: https://doi.org/10.56238/tfisdwv1-020